2023
DOI: 10.3390/nano13060982
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Nano Ti-Based Oxides for Dark and Photocatalysis: From Photoinduced Processes to Bioimplant Applications

Abstract: Catalysis on TiO2 nanomaterials in the presence of H2O and oxygen plays a crucial role in the advancement of many different fields, such as clean energy technologies, catalysis, disinfection, and bioimplants. Photocatalysis on TiO2 nanomaterials is well-established and has advanced in the last decades in terms of the understanding of its underlying principles and improvement of its efficiency. Meanwhile, the increasing complexity of modern scientific challenges in disinfection and bioimplants requires a profou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 263 publications
1
12
0
Order By: Relevance
“…[31] Generally, the O1s spectra display three peaks at ~530-531, ~532, and ~535 eV, which correspond to the oxygen in TiÀ O bonds in TiO 2 , surface oxygen species, as well as associated water molecules. [34] In our study, the O1s revealed two peaks: one representing lattice oxygen from TiO 2 and the other from surface oxygen. Notably, we didn't detect surface associate water molecule peak (Figure 1S).…”
Section: Characterizationsupporting
confidence: 50%
See 1 more Smart Citation
“…[31] Generally, the O1s spectra display three peaks at ~530-531, ~532, and ~535 eV, which correspond to the oxygen in TiÀ O bonds in TiO 2 , surface oxygen species, as well as associated water molecules. [34] In our study, the O1s revealed two peaks: one representing lattice oxygen from TiO 2 and the other from surface oxygen. Notably, we didn't detect surface associate water molecule peak (Figure 1S).…”
Section: Characterizationsupporting
confidence: 50%
“…Oxygen is present in two chemical environments in all samples, with peaks at ~529.7±0.1 and 531.2±0.1 eV corresponding to TiO 2 lattice and surface oxygen, respectively [31] . Generally, the O1s spectra display three peaks at ~530‐531, ~532, and ~535 eV, which correspond to the oxygen in Ti−O bonds in TiO 2 , surface oxygen species, as well as associated water molecules [34] . In our study, the O1s revealed two peaks: one representing lattice oxygen from TiO 2 and the other from surface oxygen.…”
Section: Resultsmentioning
confidence: 94%
“…[ 3,8 ] Furthermore, large specific surface area, high crystallinity and anatase phase are known to increase photocatalytic activity. Intense investigations are still ongoing on different aspects of photocatalytic activity of TiO 2 , which can be exploited to improve its performances, including doping and co‐doping, [ 9 ] nanostructuring, [ 10 ] defect engineering, [ 11,12 ] reactor configuration, [ 13 ] heterostructuring, [ 14 ] among the others.…”
Section: Introductionmentioning
confidence: 99%
“…The roughness, topography, surface energy, and chemistry of the metal surface can be used to control the processes at the implant-tissue interface. [36][37][38][39] Conversely, established surface treatments for Ti-based biomaterials are mostly not applicable to the BMG class. Initial studies have proposed chemical surface processing methods for Ti-Cu-based BMGs.…”
mentioning
confidence: 99%